IMPROVEMENT ON SEVERAL PHYSICAL AND MECHANICAL PROPERTIES OF JATI UTAMA NUSANTARA WOOD BY THERMAL COMPRESSION TREATMENT - Efrida Basri; Saefudin (BRIN Publishing, 2021)
Jati Utama Nusantara (JUN) is one type of growing regime of fast grown teak (Tectona grandis Linn. F) derivedfrom Jati Plus Perhutani (JPP). JUN trees have fewer branches and a more cylindrical-shaped trunk, as well asexhibit rapid growth compared to the teak cultivated from seed (conventional); accordingly, they can beharvested in a shorter time. Despite its fast growth, some studies showed that the wood had not met the SNI01-0608 standard as raw material for furniture. The research aimed to improve several physical and mechanicalproperties of young JUN wood through thermal compression treatment. The test sample for 5-year-old JUNwood was prepared with a size of 2.5 cm (thickness/radial) by 10 cm (width/tangential) by 30 cm(length/longitudinal), then compressed using a 25 kg/cm2-pressure for 40 minutes in three temperaturetreatments of 170°C, 180°C, and 190°C. Testing of wood mechanical and physical properties referred to ASTMD143. The wood crystallinity was observed using an X-Ray Diffractometer (XRD), and the wood surface wasobserved visually. Wood cell structure as supporting data was observed using a stereo-capable microscope(Zeiss). The results revealed that the thermal compression could improve the physical and mechanicalproperties of the densified JUN samples compared to the nonthermally compressed samples. Based on datasimulation, the wood samples' best physical and mechanical properties occurred at approximately 185°C's heatpress.